Nonsurgical Rhinoplasty: Long-Term Follow-Up of High G′ HA Nasal Injections - Bertossi, Dario; Magagnotto, Nicola; Chirumbolo, Salvatore; D'Souza, Alwyn; Nocini, Riccardo (Facial Plastic Surgery, 2022)
Rhinoplasty is one of the most requested aesthetic procedures performed by plastic surgeons world-wide and nonsurgical rhinoplasty is becoming the gold standard in aesthetic nasal treatment. Follow-up clinical examinations were performed on all 107 patients, being a safe and predictable technique with a high degree of satisfaction for the patients. Nonsurgical rhinoplasty using hyaluronic acid is an effective, fast, and safe nasal reshaping procedure with a high degree of patient satisfaction. Generally, due to the gradual reabsorption of the filler, the results last up to 8 to 12 months after treatment, making it a valid minimally invasive alternative to surgical rhinoplasty. Consequently, to maintain the effects it is necessary to repeat the treatment once a year.
Keywords: rhinoplasty; hyaluronic acid; nonsurgical rhinoplasty; facial; aesthetic